Nanofabrication of Biochar from Cellulosic Waste for Bio-Sensing Application of Waste Water Treatment: Process, Challenges and Future Update - Singh R.; Bansal S.L.; Tripathi S.C.; Ahmad I.; Srivastava N. (My University, 2025)
Waste water pollution is one of the most prominent concerns across the globe due to its severe impact on human health and environment which affects the ecosystem directly. Therefore, for sustainable and consistence environment, waste water treatment is the primary and mandatory agenda of agencies involve worldwide to rectify this issue. Additionally, among various sustainable trail based strategies for waste water treatment, biochar catalyst utilization is very potential and impactful whereas, use of nanoform of biochar which is also known as nanobiochar is more impactful in waste water pollution remediation. Therefore, the present review represents the sustainable fabrication of nanobiochar from organic waste biomass and process strategy for its reduction from bulk form to nano form using different sustainability procedures. Type and mode of action of different biomass, types, fabrication, methods and functional properties along with their functional efficacy have been highlighted and discussed in the review. Existing challenges and sustainable possibilities to overcome them have also discussed as future prospects for sustainable and promising application of nanobiochar as potential sensor foreco-friendly remediation of waste water pollution. © Association of Microbiologists of India 2024.